Quality assurance data for regional drip-and-ship strategies- gearing up the transfer process - Boss, Erendira G. (Neurol Res Pract, 2021)
BACKGROUND: Stroke patients with large vessel occlusion (LVO) require endovascular therapy (EVT) provided by comprehensive stroke centers (CSC). One strategy to achieve fast stroke symptom ‘onset to treatment’ times (OTT) is the preclinical selection of patients with severe stroke for direct transport to CSC. Another is the optimization of interhospital transfer workflow. Our aim was to investigate the dynamics of the OTT of ‘drip-and-ship’ patients as well as the current ‘door-in-door-out’ time (DIDO) and its determinants at representative regional German stroke units. METHODS: We determined the numbers of all EVT treatments, ‘drip-and-ship’ and ‘direct-to-center’ patients and their median OTT from the mandatory quality assurance registry of the federal state of Hesse, Germany (2012–2019). Additionally, we captured process time stamps from primary stroke centers (PSC) in a consecutive registry of patients referred for EVT in our regional stroke network over a 3 months period. RESULTS: Along with an increase of the EVT rate, the proportion of drip-and-ship patients grew steadily from 19.4% in 2012 to 31.3% in 2019. The time discrepancy for the median OTT between ‘drip-and-ship’ and ‘direct-to-center’ patients continuously declined from 173 to 74 min. The largest share of the DIDO (median 92, IQR 69–110) is spent with the organization of EVT and consecutive patient transfer. CONCLUSIONS: ‘Drip-and-ship’ patients are an important and growing proportion of stroke patients undergoing EVT. The discrepancy in OTT for EVT between ‘drip-and-ship’ and ‘direct-to-center’ patients has been reduced considerably. Further optimization of the DIDO primarily aiming at the processes after the detection of LVO is urgently needed to improve stroke patient care. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s42466-021-00136-x.